2000
DOI: 10.1105/tpc.12.3.419
|View full text |Cite
|
Sign up to set email alerts
|

The Thylakoid FtsH Protease Plays a Role in the Light-Induced Turnover of the Photosystem II D1 Protein

Abstract: The photosystem II reaction center D1 protein is known to turn over frequently. This protein is prone to irreversible damage caused by reactive oxygen species that are formed in the light; the damaged, nonfunctional D1 protein is degraded and replaced by a new copy. However, the proteases responsible for D1 protein degradation remain unknown. In this study, we investigate the possible role of the FtsH protease, an ATP-dependent zinc metalloprotease, during this process. The primary light-induced cleavage produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
213
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 351 publications
(219 citation statements)
references
References 52 publications
4
213
2
Order By: Relevance
“…We hypothesize that the increase enables P. patens to maintain a constant level of photosynthesis during the stress. Chloroplast ftsH protease is the most well characterized protease of the thylakoid membranes and is involved in the turnover of photosynthetic protein complexes (Lindahl et al 2000). Its up-regulation likely helps maintain the integrity of the chloroplast protein complexes and, hence, the eYciency of photosynthesis.…”
Section: Maintenance Of Anabolismmentioning
confidence: 99%
“…We hypothesize that the increase enables P. patens to maintain a constant level of photosynthesis during the stress. Chloroplast ftsH protease is the most well characterized protease of the thylakoid membranes and is involved in the turnover of photosynthetic protein complexes (Lindahl et al 2000). Its up-regulation likely helps maintain the integrity of the chloroplast protein complexes and, hence, the eYciency of photosynthesis.…”
Section: Maintenance Of Anabolismmentioning
confidence: 99%
“…Precisely regulated PSII repair processes involve the degradation of damaged PSII subunits and their de novo synthesis to restore photosynthetic function. The most extensively studied PSII repair process is the light-induced turnover of the D1 protein of the reaction center (RC) in which the FtsH 1-2-5-8 and Deg1-2-5-8 families of proteases have been implicated (Lindahl et al 2000;Sakamoto 2003;Kapri-Pardes et al 2007;Sun et al 2007a, b). However, the involvement of Deg2 in D1 proteolysis is questionable, since the in vitro degradation of D1 occurs in Deg2-null mutant background in A. thaliana (Huesgen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1A,B). Additionally, it has been reported that D1 protein is subjected to both chilling-and salt stress accompanied by high irradiance (Murata et al 1992, Vonshak et al 1996, Lindahl et al 2000, Allen and Ort 2001, Sudhir and Murthy 2004. Salt stress enhanced photoinhibition by inhibiting repair of PSII, i.e.…”
Section: Discussionmentioning
confidence: 98%